EFL University Students' Self-Regulated Writing Strategies: The Role of Individual Differences - Atik Umamah; Niamika El Khoiri; Utami Widiati; Anik Nunuk Wulyani (National Research University Higher School of Economics, 2022)
Background. Self-regulated learning strategies play an essential role in the success of students' learning of writing. The use of these strategies might be influenced by the student's individual differences. Purpose. This study was conducted to describe EFL university students' preferences for self-regulated writing strategies. It also examined the different use of self-regulated writing strategies by considering gender, interest in English writing, and writing achievement. Further, it measured the predictive effects of self-regulated writing strategies on the students' writing achievement. Methods. This research applied a quantitative approach and involved 58 English students. The students were required to respond to a self-report survey using the Self-Regulated Learning Strategy Questionnaire. The students' writing achievement was measured based on their scores in writing an argumentative essay. The data were then analyzed using descriptive statistics, an independent sample t-test, One Way Anova, and multiple regression. Results. The results uncovered that the overall use of self-regulated writing strategies was at a high level with the social environment strategy dimension on the top rank and motive on the bottom. Further analysis showed that there is no significant difference in the use of self-regulated writing strategies based on gender, interest in English writing, and writing achievement. Meanwhile, multiple regression analysis indicated the predictive effect of self-regulated writing strategies on writing achievement. To this end, teachers need to encourage students to use self-regulated writing strategies more optimally to enhance their writing quality. Conclusion. EFL students have invested high awareness of using self-regulated writing strategies. Along with this high awareness, students' individual differences such as gender, interest in English writing, and proficiency level might not strongly influence the use of SRW strategies. Though not strong, the use of self-regulated writing strategies contributes to the students' writing quality improvement.